Looked Class, Talked Red: towards a bio-bibliography of Ruth First. (January 2019) - Harlow, Barbara
This article includes material from a work-in-progress, Barbara Harlow's major book on South African writer and political activist, Ruth First, assassinated in 1982. Ruth First's own life followed many paths, intersecting along the way with several historical trajectories, national narratives that remain incomplete today, and political events and eventualities that are still being negotiated, contested and resisted. The author follows these paths in an attempt to locate a framework and a direction for writing what she calls a bio-bibliography, an intellectual biography that is at once a political history.